Strategi Percepatan Sertifikasi ISPO di Perkebunan Kelapa Sawit Swadaya - Hadi, Syaiful; Bakce, Djaimi; Muwardi, Didi; Yusri, Jum'arti; Septya, Fanny (Analisis Kebijakan Pertanian, 2025)
The Indonesian Sustainable Palm Oil (ISPO) certification for plantation companies and smallholder plantations has been mandated by Presidential Regulation Number 44 year 2020. Although the certification requirement has been in effect since March 2020 and will become mandatory in 2025, the performance of ISPO certification in smallholder oil palm plantations, particularly independent (self-subsistence) oil palm plantations, is still very low. This study aims to develop a strategy to expedite ISPO certification in independent oil palm plantations. This research was conducted in Riau Province, and data was gathered from samples of independent oil palm smallholders and experts. Data were analyzed using SWOT (Strengths-Weaknesses-Opportunities-Threats) and AHP (Analytic Hierarchy Process) analyses. Results of the study concluded that there are three main strategies for accelerating ISPO certification in independent oil palm plantations, namely (i) accelerating the implementation of the rejuvenation program of smallholder oil palm plantations (PSR), (ii) strengthening ISPO organizing institutions from the center to oil palm center districts, and (iii) providing mentoring assistance for the certification process. Acceleration of the implementation of PSR and the existence of strong ISPO institutions supported by field facilitators will strengthen independent oil palm smallholder institutions and empower stakeholders (Large Private Plantations/Large State-Owned Plantations) to assist the independent smallholders' oil palm plantations in getting ISPO certification.
Keywords: oil palm; independent oil palm smallholders pantation; ISPO certification; sustainability